FORMATION OF INFORMATIONAL COMPETENCE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS IN THE PROCESS OF TEACHING HUMANITIES - Drogaitsev О.І. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the process of information competence formation for High School Students by learning humanitarian subjects.